In Silico Screening of Antifolate Based Novel Inhibitors from Brucea mollis Wall. ex kurz Against Quadruple Mutant Drug Resistant PfDHFR - Borkakoty, Biswajyoti; Sarma, Kishore; Parida, Pratap; Prakash, Anil; Kishore Mohapatra, Pradyumna; Mahanta, Jagadish (Combinatorial Chemistry & High Throughput Screening, 2014)
Plasmodium falciparum is the most lethal form of the genus Plasmodium which causes malaria, a ‘disease of antiquity’. Globally it affects the health and socio-economic development of a large population especially in Sub-Saharan Africa and Southeast Asia. The Plasmodium falciparum dihydrofolate reductase-thymidylate synthase (PfDHFR-TS) is an important target of antimalarial drugs. Mutations at the active site of PfDHFR have resulted in decrease drug binding affinity of DHFR-inhibitors. In the present study we selected ten compounds of Brucea mollis Wall. Ex kurz and checked for their drug likeness using various computational tools and potential interactions with PfDHFR by molecular docking study. Soulameanone, a quassinoid of Brucea mollis Wall. Ex kurz showed better binding affinity when compared to pyrimethamine for both wild and quadruple mutant drug resistant PfDHFR. In addition, similar isomers of soulameanone were screened for their drug likeness and to study their interactions with PfDHFR. Twenty three compounds showed better binding affinity compared to soulameanone.
Keywords: Brucea mollis